Migration and refugee law : principles and practice in Australia / John Vrachnas [and others]. - Vrachnas, John (Cambridge University Press, 2012)
Migration and Refugee Law: Principles and Practice in Australia is a comprehensive overview of the legal principles governing the entry of people into Australia. This fully revised third edition provides an accessible analysis of the theory and practice of this complex and controversial area of the law. It considers the social and political context of migration and refugee law in devising innovative policies aimed at creating an equitable and rational immigration system. Migration and Refugee Law: Principles and Practice in Australia combines an astute consideration of theory with the creation of practical policy solutions, and is therefore an essential resource for migration lawyers and agents, government employees, students, judicial officers and policymakers.